Enhancing Structural Vibration Damping in Marine Machinery: A Comprehensive Numerical Investigation with Modal and Harmonic Analysis - Rath, Sangram; Sharma, Gaurav; Kumaraswamy, Adepu (Applied mechanics and materials, 2024)
This article presents a comprehensive study on the damping of vibrations in a motor-pump assembly using viscoelastic and constrained layer damping treatments. The assembly's structural model, designed using SolidWorks software, is subjected to modal and harmonic analyses in ANSYS. The primary goal is to mitigate vibration amplitudes originating from the motor and pump to enhance the assembly's operational performance. Three damping treatments are investigated: Free Layer Damping (FLD), Sandwich Constrained Layer Damping (CLD), and a novel Multilayer CLD approach. The viscoelastic material is modeled using the Prony series method, and its properties are incorporated into the finite element analysis Results demonstrate that the application of damping treatments significantly reduces vibration amplitudes compared to the untreated structure. Among the treatments, the Multilayer CLD approach exhibits the highest damping efficiency, reducing the maximum amplitude by approximately 52% compared to the base structure. The study showcases the advantages of utilizing viscoelastic and constrained layer damping techniques for enhancing vibration control and operational stability in industrial assemblies. The research findings contribute to the field of structural dynamics and vibration control, offering valuable insights into the design and optimization of mechanical systems subjected to dynamic loads. This study opens avenues for further research and practical applications aimed at improving the performance and reliability of motor-pump assemblies and similar industrial equipment.